(untitled) (Research, Society and Development, 2021)
Objective: to analyze the epidemiological profile of suicide cases in Paraíba/Brazil, from 2015 to 2019. Methods: data were collected from the Mortality Information System (MIS) and analyzed according to the categories of intentional self-harm (X60 to X84) of the International Classification of Diseases (ICD-10), examining the distributions by gender, race, age group, education and region of residence. Results: a total of 1,140 deaths were registered, mainly of people with active working age from 20 to 59 years (73.4%). The majority was male (78.0%), with a slight predominance in the 30-39 age group (20.0%), single (more than 25%), brown (more than 60%), with 4 to 7 years of schooling (6.3%); the primary method used was category X70 (hanging, strangulation and suffocation) with 83.0%. Conclusion: suicide mortality continues to grow in Paraíba and varies according to gender and colour, being higher in the microregions of João Pessoa and Campina Grande. Thus, are necessary promotion, prevention and monitoring strategies in social action and mental health care, with significant regional variations.